HAK HAK YANG DIPEROLEH PADA ANAK PENGIDAP AUTISME DI SEKOLAH DASAR UMUM DI KABUPATEN BUNGO - Salimatunnisa, Salimatunnisa; Shiddiq, Nur; Andriani, Opi; Novalia, Ratih Juwita (Jurnal Pendidikan Vokasi dan Seni, 2023)
This research aims to identify the rights obtained by children with Autism in Public Elementary Schools in Bungo Regency. Autism is a developmental disorder that affects social interactions, communication, and individual behavior. Although children with autism have rights that need to be recognized and fulfilled in an educational environment. This research uses a qualitative approach with in-depth interviews and observation as data collection methods. This research was carried out on 6th grade students with autism at the Elementary School in Muara Bungo, totaling 2 students. The results of this research show that children with Autism in Public Elementary Schools in Bungo Regency have rights that need to be recognized and fulfilled, such as; inclusive education, specialized support, participation, protection and full development are important rights for children with Autism.